Review of scenario planning and future strategy of PT. Telkomsel's fixed mobile convergence (FMC) service implementation - Teguh Bayu Aji Riawan; Rina Djunita Pasaribu; Moh. Riza Sutjipto (Goodwood Publishing, 2025)
Purpose: This abstract provides a brief overview of a review article that explores the scenario planning approach and future strategies for the implementation of Fixed Mobile Convergence (FMC) services by PT. Telkomsel. This study aimed to analyze the limitations and contributions of scenario planning in shaping future strategies for FMC service implementation. Research methodology: This study uses a scenario planning method that aims to identify the driving forces for the future of the telecommunications industry in Indonesia in 2030 and then formulates a scenario for the future of telecommunications services in Indonesia. These scenarios are used as the basis for recommendations for PT. Telkomsel's business strategy for implementing FMC services, which is carried out through a qualitative approach. Results: The research results found that, in the future, network coverage and technology will no longer be a competitive advantage for telecommunications companies in Indonesia. The research results show four possible future scenarios for the telecommunications industry in Indonesia: New Glory, Win Back Domination, Digital Colonialism, and Business as Usual. Conclusion: PT. Telkomsel must always invest in additional infrastructure to meet customer bandwidth needs. The implementation of FMC services is crucial to increase the company's competitive advantage, but it requires careful anticipation of volatile, uncertain, complex, and ambiguous (VUCA) conditions to minimize future business risks. Scenario planning becomes necessary to develop an adaptive and resilient corporate strategy. Limitation: This study is limited to scenario planning analysis based on qualitative data and focuses on Indonesia's telecommunications industry context toward 2030. Contribution: The study contributes to providing strategic insights and future-oriented recommendations for PT. Telkomsel to optimize FMC service implementation under potential industry changes.